2006
DOI: 10.1097/01.jom.0000204114.01893.3e
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Manganese-Induced Occupational Parkinsonism With p-Aminosalicylic Acid: A Case of 17-Year Follow-Up Study

Abstract: Objective-Chronic manganese (Mn) intoxication induces syndromes resembling Parkinson disease. The clinical intervention has largely been unsuccessful. We report a 17-year follow-up study of effective treatment of occupational Mn parkinsonism with sodium para-aminosalicylic acid (PAS).Methods-The patient, female and aged 50 at the time of treatment, was exposed to airborne Mn for 21 years . The patient had palpitations, hand tremor, lower limb myalgia, hypermyotonia, and a distinct festinating gait. She receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 26 publications
(32 reference statements)
4
107
0
2
Order By: Relevance
“…Our previous work on a manganism patient treated with paraaminosalicylic acid showed a normal T1-weighted MRI in the globus pallidus (Jiang et al, 2006). Kim and his colleagues have reported that a welder with more than 10-year Mn exposure whose clinical manifestations included masked face, asymmetric resting tremor, and bradykinesia had symmetrical high signal intensities in the globus pallidus on T1-weighted image.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work on a manganism patient treated with paraaminosalicylic acid showed a normal T1-weighted MRI in the globus pallidus (Jiang et al, 2006). Kim and his colleagues have reported that a welder with more than 10-year Mn exposure whose clinical manifestations included masked face, asymmetric resting tremor, and bradykinesia had symmetrical high signal intensities in the globus pallidus on T1-weighted image.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the mechanism of Mn neurotoxicity and identify the potential susceptibility of cell types to Mn exposure, it is necessary to have thorough understanding of the intracellular distribution of Mn within different types of brain cells. In our recent attempt to explore the mechanism of para-aminosalicylic acid (PAS) in effective treatment of manganism patients (Jiang et al, 2006), there is a need to study whether and how this drug may mobilize the intracellular pool of Mn. Thus, the purpose of this study was to determine and compare the subcellular distribution of Mn in cell types that are important for Mn transport and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, levodopa is contraindicated in manganism, as Mn catalyzes dopamine autooxidation to toxic quinones and semiquinones (Graham 1984;Lloyd 1995;Parenti et al 1988). According to some studies (Discalzi et al 2000;Herrero Hernández et al 2003;Herrero Hernández et al 2006;Ky et al 1992;Ono et al 2002;Penalver 1957) chelating treatment can reverse manganese poisoning with persistent clinical benefit for many years (Herrero Hernández et al 2003;Herrero Hernández et al 2006;Jiang et al 2006). However, large controlled clinical trials are lacking.…”
Section: Treatmentmentioning
confidence: 99%